The happiness effect of high-quality development of China’s health and wellness industry: micro-empirical evidence from the Chinese Social Survey 2013–2021 - Liu, Song; Zhu, Wei (Frontiers in Public Health, 2025)
BackgroundChina has experienced more than 40 years of rapid economic growth and is rapidly entering a deeply aging society. The health needs of Chinese residents have shifted from survival-oriented healthcare to quality-oriented health and wellness services. Promoting the high-quality development of the health and wellness industry is essential for improving national health outcomes and enhancing residents’ overall well-being. While prior research has primarily examined micro-level factors such as older adults care models and medical insurance, empirical studies investigating the happiness effect of industry-level development remain limited.MethodsThis study draws on data from five waves of the Chinese Social Survey (CSS) conducted between 2013 and 2021. A comprehensive indicator system was constructed to measure the high-quality development of China’s health and wellness industry. An ordered logistic regression model was employed for empirical analysis, while also exploring underlying mechanisms and subgroup heterogeneity.ResultsThe findings indicate that the high-quality development of the health and wellness industry significantly enhances residents’ happiness. Moreover, the social security systems positively moderate this relationship. Heterogeneity analyses reveal that the happiness-enhancing effect of the high-quality development of the health and wellness industry is more pronounced among female residents, slightly stronger among younger cohorts, notably greater for urban residents, and more significant in eastern China.ConclusionThis study highlights the positive effect of the high-quality development of China’s health and wellness industry on residents’ happiness, and the positive moderating effect of the social security systems. To further enhance residents’ subjective well-being, it is essential to further improve the quality of development of China’s health and wellness industry. In addition, efforts should be made to deepen the reform of the older adults care security system to better accommodate the increasingly complex care needs of an aging society. Reforming and expanding the medical security system is also vital for improving the accessibility and equity of health services.